Optimizing The Use of Social Crowdfunding in SMEs To Encourage The Implementation of Circular Economic Practices - Mohamad Nasoha; Hubertina Karolina Ngarbingan; Ginta Ginting; Maya Maria; Zulfahmi Zulfahmi (International Journal of Applied Business and International Management, 2024)
Circular Economy (CE) is an alternative concept for switching from a linear economy (take-make-dispose) to make-use-recycle. To be able to carry out economic transformation as quickly as possible. Practically, there are big challenges and gaps with current actual conditions. So far, the CE practice approach has been more directed at technology and manufacturing changes. For large business actors, the implementation of CE practices can be accommodated because of the potential resources they have. However, for SMEs, the practice of implementing CE is still not carried out optimally due to limited resources, especially in terms of funding. One funding alternative that can be accessed is Fin Tech Crowdfunding, especially the donation-based crowdfunding (Social Crowdfunding) scheme. To gain insight into the extent to which Social Crowdfunding is used among SMEs to support CE practices, a survey was conducted in which 69 respondents participated. Survey findings analyzed descriptively indicate positive things, namely that there are some SMEs who have implemented CE principles in their business activities (reuse, reduce and recycle) which have an impact on environmental conservation. To be able to encourage the widespread implementation of CE practices, it is necessary to provide socialization and education regarding social crowdfunding to SMEs which can be an alternative funding solution. It is important to strengthen this socialization and education because the findings from this research indicate that some SMEs do not understand the benefits and how to access social crowdfunding. Important findings from extracting facts in the field and combined with the theory of willingness to participate and the AIDA concept are proposed for modeling using 3 determinants (as antecedents), namely fund resources capital, community engagement and entrepreneurship spirit which have an impact on increasing awareness and interest from SMEs to implement sustainable CE practices.